2010
DOI: 10.1007/s10916-010-9450-y
|View full text |Cite
|
Sign up to set email alerts
|

Automated Detection of Breast Cancer in Thermal Infrared Images, Based on Independent Component Analysis

Abstract: Breast cancer, among women, is the second-most common cancer and the leading cause of cancer death. It has become a major health issue in the world over the past decades and its incidence has increased in recent years mostly due to increased awareness of the importance of screening and population ageing. Early detection is crucial in the effective treatment of breast cancer. Current mammogram screening may turn up many tiny abnormalities that are either not cancerous or are slow-growing cancers that would neve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 23 publications
0
29
0
2
Order By: Relevance
“…Over several decades, with rapidly developing computer technology and artificial intelligence, DITI has been extensively studied in many fields of medical science, such as diabetic neuropathy [6], vascular disorders [7], fever screening [8], dry eye syndrome diagnosis [9], and breast cancer detection [10][11][12][13], and even as a pre-screening tool for the detection of canine bone cancer [14]. For example, it has been reported that when state-of-the-art infrared technology was combined with advanced computer hardware and software technology, the sensitivity for breast cancer detection was 97% in 92 patients undergoing breast biopsy [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over several decades, with rapidly developing computer technology and artificial intelligence, DITI has been extensively studied in many fields of medical science, such as diabetic neuropathy [6], vascular disorders [7], fever screening [8], dry eye syndrome diagnosis [9], and breast cancer detection [10][11][12][13], and even as a pre-screening tool for the detection of canine bone cancer [14]. For example, it has been reported that when state-of-the-art infrared technology was combined with advanced computer hardware and software technology, the sensitivity for breast cancer detection was 97% in 92 patients undergoing breast biopsy [15].…”
Section: Introductionmentioning
confidence: 99%
“…Since cancer cells with their higher metabolic rate are hotter than normal cells, which makes cancerous tumors appear as hotspots in DIT images, this technique is particularly useful in female breast | 180 imaging [13]. While higher-order statistics such as variance, skewness, kurtosis, and joint entropy are effective measures of asymmetry [13], there are other technical methodologies to develop an automatic asymmetry analysis system, such as independent component analysis [12], Hough transform-aided image segmentation and pattern classification [16], and fuzzy logic [17].…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer, among women, is the second-most common cancer and the leading cause of cancer death. It has become a major health issue in the world over the past decades and its incidence has increased in recent years mostly due to increased awareness of the importance of screening and population ageing (Boquete et al, 2012). Currently, mammography is the dominant method for detection of breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, ICA has been used for image segmentation [30] and medical image analysis [8,19,41]. Boquete et al [8] have proposed a thermographic image analysis based on ICA for automated detection of high tumor risk areas.…”
Section: Introductionmentioning
confidence: 99%
“…Boquete et al [8] have proposed a thermographic image analysis based on ICA for automated detection of high tumor risk areas. Hassen et al [19] used ICA to built a cardiovascular disease diagnosis system based on magnetic resonance imaging.…”
Section: Introductionmentioning
confidence: 99%